Impact of liposomal delivery on coenzyme Q10 absorption: a double-blind, placebo-controlled, randomized trial - Jäger, Ralf; Purpura, Martin; Godavarthi, Ashok; Ceylan, Halil Ibrahim; Balcombe, Sebastian T.; Chandrappa, Ambrish; Tinsley, Grant M. (Frontiers in Nutrition, 2025)
BackgroundCoenzyme Q10 (CoQ-10) plays a vital role in cellular energy production and protection against oxidative stress. However, its absorption from orally administered forms is limited due to its poor water solubility and relatively large molecular weight. While co-ingesting CoQ-10 with a fatty meal can enhance absorption, this approach is not always practical. The aim of this study was to evaluate whether a liposomal formulation of CoQ-10 could improve its absorption compared with standard CoQ-10 without the need for the concurrent consumption of fatty foods.MethodsIn a randomized, double-blind, placebo-controlled, crossover study design, 7 men and 11 women (n = 18; age: 33.5 ± 6.4 years, height: 171.2 ± 8.1 cm, weight: 65.6 ± 8.8 kg) ingested a single dose of placebo (PLA), 100 mg of unformulated CoQ-10, or 100 mg of liposomal CoQ-10 (Lipo CoQ-10, LipoVantage®, Specnova, LLC, Tyson Corner, VA, USA). Venous blood samples were collected at 0, 0.5, 1, 1.5, 2, 3, 4, 6, 8, 12, and 24 h after ingestion and analyzed for plasma CoQ-10 concentrations.ResultsCoQ-10and Lipo CoQ-10 demonstrated significantly greater Cmax and AUC0-24 compared with placebo (p < 0.001). Additionally, Lipo CoQ-10 had significantly higher Cmax (+31.3%, p < 0.001) and AUC0-24 (+22.6%, p < 0.001) values as compared with CoQ-10. CoQ-10 formulations were well-tolerated, with no significant changes in safety markers (blood pressure, renal function, liver enzymes, and lipid profile; p > 0.05), indicating a favorable safety profile.ConclusionLiposomal delivery significantly enhances CoQ-10 absorption.Clinical trial registrationhttps://www.ctri.nic.in identifier CTRI/2024/04/066483.